Tunable room-temperature single-photon emission at telecom wavelengths from sp3 defects in carbon nanotubes - He, Xiaowei; Hartmann, Nicolai F.; Ma, Xuedan; Kim, Younghee; Ihly, Rachelle; Blackburn, Jeffrey L.; Gao, Weilu; Kono, Junichiro; Yomogida, Yohei; Hirano, Atsushi; Tanaka, Takeshi; Kataura, Hiromichi; et al. (Nature photonics, 2017)
Generating quantum light emitters that operate at room temperature and at telecom wavelengths remains a significant materials challenge. To achieve this goal requires light sources that emit in the near-infrared wavelength region and that, ideally, are tunable to allow desired output wavelengths to be accessed in a controllable manner. Here, we show that exciton localization at covalently introduced aryl sp 3 defect sites in single-walled carbon nanotubes provides a route to room-temperature single-photon emission with ultrahigh single-photon purity (99%) and enhanced emission stability approaching the shot-noise limit. Moreover, we demonstrate that the inherent optical tunability of single-walled carbon nanotubes, present in their structural diversity, allows us to generate room-temperature single-photon emission spanning the entire telecom band. Single-photon emission deep into the centre of the telecom C band (1.55 µm) is achieved at the largest nanotube diameters we explore (0.936 nm). Single-photon emission with 99% purity is generated from sp 3 defects in carbon nanotubes (CNTs) by optical excitation at room temperature. By increasing the CNT diameter from 0.76 nm to 0.94 nm, the emission wavelength can be changed from 1,100 nm to 1,600 nm.